The Multiple Deficit Model: Progress, Problems, and Prospects - McGrath, Lauren M.; Peterson, Robin L.; Pennington, Bruce F. (Scientific studies of reading, 2020)
The multiple deficit model (MDM) was proposed because the prevailing single deficit model provided an inadequate account of atypical neuropsychological development. Across methods and levels of analysis, there has been support for the two fundamental tenets of the MDM, that multiple predictors contribute probabilistically to neurodevelopmental disorders and shared risk factors contribute to comorbidity. Diagnostically, the multiplicity of factors means that no single cognitive deficit or combination of deficits can be used to rule in or out most neurodevelopmental disorders. Challenges for the MDM are that the theory is difficult to falsify and that current cross-sectional studies cannot establish causality. Prospects for further development of the MDM include incorporating an explicit focus on promotive and protective factors and pursuing mechanistic connections between multiple factors across levels of analysis.